2015
DOI: 10.1167/tvst.4.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Lens Fragmentation Using Femtosecond Laser: An In Vitro Study

Abstract: Purpose: To transect intraocular lenses (IOLs) using a femtosecond laser in cadaveric human eyes. To determine the optimal in vitro settings, to detect and characterize gasses or particles generated during this process.Methods: A femtosecond laser was used to transect hydrophobic and hydrophilic acrylic lenses. The settings required to enable easy separation of the lens fragment were determined. The gasses and particles generated were analysed using gas chromatography mass spectrometer (GC-MS) and total organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, our experience demonstrates that the technical requirements are similar in patients with PIOL because modifications were not made and no capsulotomy tags were found intraoperatively. A previous in vitro study revealed that the IOL can be transected by using the minimum laser energy of 1 μJ [ 10 ]. This indicates that PIOL produces a small decrease in laser power.…”
Section: Discussionmentioning
confidence: 99%
“…However, our experience demonstrates that the technical requirements are similar in patients with PIOL because modifications were not made and no capsulotomy tags were found intraoperatively. A previous in vitro study revealed that the IOL can be transected by using the minimum laser energy of 1 μJ [ 10 ]. This indicates that PIOL produces a small decrease in laser power.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study showed that IOL fragmentation was feasible with FSL [113]. Anisimova et al [114] introduced a case in which a one-piece acrylic hydrophobic IOL was successfully transected using FSL with low energy parameters for explantation via a small corneal incision.…”
Section: Experimental Studies Regarding Potential Application Of the mentioning
confidence: 99%